Fuzzy Logic in Inverse Continuous Method - Víťazoslav Krúpa; Ľudmila Ušalová; Edita Lazarová (Acta Montanistica Slovaca, 2004)
In the field of geotechnics, certain vagueness and ambiquity appears. We might not be able to design a mathematically accuratedescription of rock, whose properties change during the excavation (rock strength, discontinuities direction, dislocations, rock type).Furthermore, the excavation regime (thrust, revolutions, torque) changes too, as well as the edge angle of cutting tools (due to wear) andworking ability of cutterhead as result of sequential exchanges of worn-out cutterhead discs. All of these facts cause that the cutterheadoperates using the discs with different wear stage. The above mentioned problems led us to the decision to use the fuzzy logic and fuzzy sets,e.g. techniques operating with vagueness and ambiguity.